An investigation of women's pregnancy experiences during the COVID‐19 pandemic: A qualitative study. Issue 9 (10th June 2021) - Aydin, Ruveyde; Aktaş, Songül
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has adversely affected the physical and psychosocial health of pregnant women and their access to antenatal care and health services. Aim: To examine women's pregnancy experiences during the COVID‐19 pandemic. Materials and methods: The study was conducted in a qualitative design with 14 pregnant women who were admitted to a state hospital pregnancy outpatient clinic for antenatal control. The data were collected using a semi‐structured individual interview form and were analysed using the thematic analysis technique. COREQ checklist guide was followed in the study. Results: The pregnancy experiences of women in the COVID‐19 pandemic were examined under 7 main themes: "physical health, psychosocial health, adaptation to pregnancy, pregnancy follow‐ups, social life, spouse relationship and coping methods". Pregnant women have both positive and negative pregnancy experiences in the COVID‐19 pandemic. Conclusion: The study concluded that the pandemic has affected both the physical and psychosocial health of pregnant women, their social life, marital relationship and access to antenatal care services. Health professionals need to evaluate psychosocial health as well as the physical health of pregnant women, especially during the pandemic, and create a care plan accordingly. Midwives and other health professionals should improve the bio‐psychosocial health of the pregnant/family via telehealth and counselling services.